Genus Ablerus Howard (Hymenoptera: Chalcidoidea: Aphelinidae) in North America, with description of two new Mexican species - Myartseva, Svetlana N.; Coronado-Blanco, Juana María; Ruíz-Cancino, Enrique (Instituto de Ecología, A.C., 2012)
Ablerus Howard is a genus of Aphelinidae, that contains 92 species to world level. Ablerus includes primary and secondary parasitoids of other insects. This article provides the key to identify females of the seven species of this genus occurring in North America and also describes two new species. Until today three species are known from Mexico, and eight species from North America.